DESIGNING A SYLLABUS FORA COURSE OF ENGLISH FOR SECRETARY BASED ON INTERVIEWS WITH PROFESSIONAL SECRETARIES: A CASE STUDY - Anna Marietta Da Silva (Soegijapranata Catholic University, 2010)
The job of a secretary is probably one of the most popular vacancies advertised in Indonesian mass-media. Many profit and non-profit organizations seekfor professional secretaries because of the central role the profession holds. A secretary is an assistant to her employer, and oftentimes she becomes not only lithe hands